Characteristics and Mechanism of Styrene Cationic Polymerization in Aqueous Media Initiated by Cumyl Alcohol/B(C6F5)3. Issue 4 (2nd January 2019) - Zhang, Jinghan; Wu, Yibo; Li, Xiaoning; Yang, Dan; Zhang, Min; Wang, Hao; Shang, Yuwei; Ren, Ping; Mu, Xin; Li, Shuxin; Guo, Wenli
Abstract: Styrene cationic polymerizations initiated by cumyl alcohol (CumOH)/B(C6 F5 )3 are systematically studied in aqueous suspension and emulsion. Theoretical calculations and experimental research suggest that CumOH/B(C6 F5 )3 has higher initiating activity than H2 O/B(C6 F5 )3 . During emulsion polymerization of styrene, molecular weight and polymerization rate decrease with the addition of surfactants. These polymerization processes share the same features. Specifically, all elemental reactions (initiation, propagation, and termination) in aqueous media occur at the droplet interface. End structure analysis indicates that chain transfer reactions to water and a ‐proton elimination and chain transfer reactions to monomer occur. The possible mechanism for the styrene cationic polymerization in aqueous media is demonstrated. Abstract : Poly(styrene)s are successfully synthesized in aqueous media by using cumyl alcohol initiating system. All elemental reactions (initiation, propagation, and termination) in aqueous media occur at the droplet interface. Chain transfer reactions to water and β‐proton elimination and chain transfer reactions to monomer occur. The polymerization characteristics and corresponding polymerization mechanism are investigated.